NILAI-NILAI KESADARAN SEJARAH DAN PENDIDIKAN KARAKTER BANGSA SEBAGAI DASAR PEMBENTUK PERILAKU SOSIAL UNTUK MEMPERTAHANKAN IDEOLOGI BANGSA - Neli Filhi Lijulli Afni; Sarkadi Sarkadi; Nurzengky Ibrahim (Jurnal Pendidikan Sejarah Indonesia, 2021)
This article aims to explain the values of historical consciousness and national character education as a basis for shaping social behavior to defend the nation's ideology. This research is a literature study. Pancasila ideology is an inspiration of the character and personality for the Indonesians. Nevertheless, Indonesian people are starting that ideology. If this is allowed to drag on, it will threaten the loss of the ideology of the nation. Enhancing historical consciousness values and national character education for all could help to overcome this problem.Historical consciousness consist of sense of awareness, self-knowledge about what has happened to one selves and the nation that makes humans want to self-reflect and imitate, and implement the values contained in the Pancasila ideology, namely being able and willing to have good social behavior.  Meanwhile, national character education is a reflection of the Pancasila ideology. So, it is very important to provide national character education from an early age so that it is accustomed and easy to behave according to Pancasila values, namely being willing and able to have good social behavior. The values of historical consciousness and national character education have been deeply embedded in a nation indirectly reflect the strength of the Pancasila ideology. Thus, maintaining the nation's ideology can be done by forming good social behavior which is instilled through historical consciousness values and national character education